Phosphorus forms and distributions in soils under selected land use practices at the Federal University of Agriculture, Abeokuta, Ogun State, Nigeria - Abiodun Olusegun, Oladoye; Mutiu Abolanle, Busari; Femi Olusola, Abiodun; Oluseyi Opeyemi, Ojekunle; Noah Alabi, Oyebamiji; Blessing Adegboyega, Olaife (Annals of Tropical Research, 2021)
The forms and distributions of phosphorus were determined for four different land use practices in Federal University of Agriculture, Abeokuta, with the aim of evaluating the effects of land use and soil depth on soil physical and chemical properties, forms and distributions of phosphorus. The study was a 4×2 factorial experiment laid out in a Randomized Complete Block Design. Factor 1 was four different land use practices (Gmelina arborea, Tectona grandis, Leucaena leucocephala plantations and secondary forest), and Factor 2 was soil samples collected from two soil depths (0-30cm and 30-60cm). The soil pH, electrical conductivity, exchangeable bases (Na, K, Mg and Ca), particle size, organic carbon, total nitrogen, total phosphorus, inorganic phosphorus fractions (Al-P, Fe-P and Al-P) and available phosphorus analyses were carried out using standard procedures. Data collected from the laboratory analysis were subjected to two-way Analysis of Variance while the means among the treatments were separated using Duncan Multiple Range Test. The results showed that the soils had low total and available P contents. The soil under Leucaena leucocephala plantation had the highest total phosphorus (111.05mg kg-1), followed by Tectona grandis (97.63mgn kg-1), Gmelina arborea (96.41mg kg-1) and secondary forest (83.63mg kg-1). Total P decreased with depths (0-30cm and 30-60cm). Inorganic P-fractions were greatly influenced by soil properties such as soil pH, soil electrical conductivity, organic carbon, and soil particle size. The inorganic phosphorus fractions of the soils in all study area occurred generally in the following sequential order; Fe-P>Ca-P>Al-P. The highest inorganic phosphorus recorded in all in the study area was Fe-P, followed by Ca-P and Al-P. Al-P had the lowest content between the depths examined. Lower nutrient concentrations in soils under secondary forest within the depths were due to lower organic matter content, higher nutrient demand, nutrient immobilization by tree species and other flora present. P fractionation investigations are therefore recommended in soils under indigenous species plantation in order to provide adequate understanding of P status in the soils and fertilizer recommendation so as to improve productivity.